MODERASI PREFERENSI RISIKO PENGARUH PEMERIKSAAN PAJAK DAN PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK - Alif Faruqi Febri Yanto; Rida Perwita Sari (Jurnal Proaksi, 2021)
The percentage of individual taxpayer compliance both as a whole and non-employees and employees in 2018-2020 has decreased in the implementation of taxpayer compliance so that an evaluation must be carried out both in terms of policies and services. This study aims to obtain empirical evidence of the direct effect of taxpayer compliance which is influenced by tax audits and tax services and the moderating effect of risk preferences on the relationship between tax audits and tax service services on taxpayer compliance. The Pratama Surabaya Mulyorejo Tax Service Office is the object to be researched. Individuals as subjects and population with the type of probability sampling and simple random sampling method as many as 87 respondents. Analysis based on components or commonly known as Generalized Structured Component Analysis (GeSCA) is the analytical technique used in this research. The results of the output in the study explain that there is empirical evidence of taxpayer compliance which is directly influenced by tax audits and tax service services. Risk preferences can moderate the effect of tax audit on taxpayer compliance. Keywords: Tax audit, tax service, risk preference and taxpayer compliance